Messianisme dalam Perspektif Filsafat Sejarah - Misnal Munir (Jurnal Filsafat "WISDOM", 2004)
The concept of messianism which was derived from religion was also found in historical thought of philosophers like Hegel, Karl Marx, Auguste Comte, Berdyaev. Messianism was symbolised, in the philosophical context had been understood as the tops of histrorical development.